Analisis Pengendalian Persediaan Kertas pada PT. JKL Menggunakan Metode Algoritma Wagner Within - Putri, Chitra Meisya; Nurainun, Tengku; Hartati, Misra; Nazaruddin, Nazaruddin; Nur, Muhammad (Fakultas Teknik Universitas Tulang Bawang, 2026)
The intense competition in the printing industry demands companies to improve efficiency, particularly in managing raw material inventories. PT. JKL faces challenges in controlling paper inventory, including excessive stock reaching up to 32,000 kg per year and inefficient ordering and shipping costs due to mismatches between order quantity and truck capacity. These issues lead to increased costs and the risk of stockouts or overstocking. The purpose of this study is to identify the most efficient quantity and schedule for paper ordering while keeping overall inventory costs low using the WWA (Wagner Within Algorithm) method. A quantitative approach is employed, involving demand forecasting, WWA calculation, safety stock, and reorder point analysis. The results indicate that implementing the WWA method can reduce the number of orders from 24 to 12 annually and achieve inventory cost savings of Rp 375,368,025. Additionally, the company can maintain a safety stock level 3,411 kg and a reorder point set of 13,204 kg. Thus, the WWA method is effective in addressing PT. JKL’s inventory control problems and can be adopted as a strategic tool for operational efficiency. Keywords: Demand Forecasting, Inventory Control, Inventory Cost, Wagner Within Algorithm